Analisa Kekuatan Mekanik Sambungan Las Menggunakan Pola Ayunan Melingkar Dan Zig-Zag Pada Baja Karbon Sedang - Irwan, Irwan; Endriatno, Nanang; Hasanudin, La (Teknik Mesin Universitas Halu Oleo, 2022)
Welding is one of the metal joining techniques by melting some of the parent metal and filler metal which is currently widely used with different methods and movements of welding electrodes. These methods aim to obtain flat and smooth welds and at the same time become the impetus for the compilers to conduct research entitled